12.2k views
2 votes
Simplify the expression (8x^3y^2/4a^2b^4)^-2

A. 4x^6y^4/a^4b^8
B. a^4b^8/2x^6y^4
C. a^4b^8/4x^6y^4
D. a^4b^6/2x^5y^4

1 Answer

4 votes
Simplify the following:
((8 x^3 y^2 a^2 b^4)/4)^(-2)
8/4 = (4×2)/4 = 2:
(2 x^3 y^2 a^2 b^4)^(-2)
Multiply each exponent in 2 x^3 y^2 a^2 b^4 by -2:
(x^(-2×3) y^(-2×2) a^(-2×2) b^(-2×4))/(2^2)
-2×3 = -6:
(x^(-6) y^(-2×2) a^(-2×2) b^(-2×4))/2^2
-2×2 = -4:
(y^(-4) a^(-2×2) b^(-2×4))/(2^2 x^6)
-2×2 = -4:
(a^(-4) b^(-2×4))/(2^2 x^6 y^4)
-2×4 = -8:
b^(-8)/(2^2 x^6 y^4 a^4)
2^2 = 4:
Answer: 1/(4 x^6 y^4 a^4 b^8) thus the answer is A
User Vural
by
5.8k points